Padmarajan’s creative illustration of masculinities - Niranjana, Jayasree; Sreenivasulu, Yadamala (Creativity Studies, 2024)
Padmarajan is an eminent personality of Indian cinema whose passionate and exquisite oeuvre of films grappled with the minds of viewers in India but remains underexplored in international academia. This article focuses on the creative representation of masculinities by Padmarajan with the aid of varied masculinity theories starting from the foundational masculinity ideas of Raewyn Connell to the alternate masculinity concepts rooted in the South Asian socio-cultural milieu. The paper examines how skilfully Padmarajan presents different forms of masculinity primarily subverting the traditional depictions in his select films.